공막 돌륭술 환자에서 피브리노겐-트롬빈 접착제를 사용한 결막 부착법의 유용성 - 박경수; Kyung Soo Park; 김상우; Sang Woo Kim; 우제문; Je Moon Woo (Daihan angwa haghoi jabji, 2013)
목적: 망막 박리가 있는 환자를 대상으로 공막 돌륭술 시행 시 파이브린 글루를 이용한 결막 부착술의 효과를 알아보고자 하였다. 대상과 방법: 공막 돌륭술을 시행 받고 3개월 이상 추적관찰이 가능하였던 총 35명 37안을 대상으로 하였다. 파이브린 글루를 이용하여 결막 부착 술 시행 후 1일째, 1주일째, 1개월째, 3개월째 환자의 불편감의 정도, 잔존 접착제 및 접착 부위의 벌어짐 유무와 감염 유무를 조사하였다. 결과: 수술 후 모든 환자에서 잔존 접착제는 관찰되지 않았으며 1명(1안)에서만 결막 부착술을 시행한 비측면 결막의 벌어짐이 관찰되었다. 수술 후 감염이나 염증은 없었으며 수술 직후부터 환자의 불편감은 통계적으로 유의하게 감소하였다(p＜0.05). 결론: 공막 돌륭술에서 파이브린 글루를 이용한 결막 부착술은 부작용이 거의 없으면서 기능적 및 미용적으로 매우 우수한 방법이며. 임상적 효과나 효용성 및 결막을 접합시키는 능력에 있어서 기존의 방법인 봉합사를 이용하여 봉합하는 방법에 대한 대체 방법으로 유용한 방법이라고 생각된다. <대한안과학회지 2013;54(12):1832-1837> Purpose: We investigated the efficacy of fibrin glue for conjunctival closure in scleral buckling operations. Methods: Thirty-seven eyes of 35 patients who underwent conjunctival closure for a scleral buckling operation with a minimum follow-up period of 3 months were evaluated. Postoperative discomfort (average score), presence of remnant adhesives, scleral buckle material infection, and wound dehiscence were evaluated prospectively in 35 eyes of 33 patients undergoing surgery with fibrin glue. Results: The eyes showed decreasing conjunctival injection and hemorrhage over time and near to full recovered without any treatment after 1 month. With time, the average discomfort score decreased significantly (p < 0.05) and wound dehiscence was found in only 1 eye. There was no adhesive remnant in any of the eyes. Conclusions: The use of fibrin glue for conjunctival closure in scleral buckling operations is excellent as a cosmetic and functional method. The glue can reduce postoperative discomfort and is especially useful as a method to replace conventional conjunctival sutures. J Korean Ophthalmol Soc 2013;54(12):1832-1837